Isolation of Polyhydroxybutyrate (PHB) Producing Bacteria, Optimization of Culture Conditions for PHB production, Extraction and Characterization of PHB - Thapa, Christina; Shakya, Pallavi; Shrestha, Rabina; Pal, Sushovita; Manandhar, Prakash (Nepal Journal of Biotechnology, 2019)
Polyhydroxybutyrates (PHBs) are energy reserves synthesized by different micro-organisms such as Alcaligenes, Pseudomonas, Staphylococcus, Algae, in excess of carbon and limitation of nutrients like nitrogen. These biopolymers are suitable alternate to synthetic carbon-based polymers. However, the high production cost limits their commercialization. The aim of this study was thus, focused on optimization of culture condition for maximum PHB production in an attempt to reduce the production cost. The micro-organisms for this purpose were isolated from 4 different soil samples and screened for PHB production. Culture conditions for these organisms were optimized by changing the parameters, viz., incubation time, pH, carbon source and NaCl concentration. Thus, optimized culture condition was used to culture the isolates for extraction of PHB and its analysis. The extracted compounds on FTIR-analysis gave characteristic C=O peak of PHB, thus, confirming the seven isolates to be PHB producers. Results for optimized parameters for the isolated PHB positive species showed that synthesis of PHB was maximum at 48 hours i.e. during the early stages of stationary phase. However, different isolates favored different culture conditions. Highest PHB accumulation and growth of isolates were seen at pH 7 and 9. Similarly, it was observed that glucose was favored by 4 isolates and sucrose was favored by 3 isolates. Interestingly, NaCl concentration did not cause significant effect on neither the bacterial growth nor the PHB production. During the extraction of PHB from the optimized culture conditions, extraction of PHB from broth gave significant yield than that from agar. A good PHB yield from broth amounting to 36.41% and 34.59% was observed for Bacillus pasteurii and Micrococcus luteus respectively, showing a potential for their exploitation in industrial PHB production. At optimized conditions, 7 isolates exhibited significant PHB yields, thus showing a potential for further exploitation.